2000
DOI: 10.1111/j.1469-7793.2000.t01-1-00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased muscle spindle sensitivity to movement during reinforcement manoeuvres in relaxed human subjects

Abstract: The effects of reinforcement manoeuvres, such as mental computation and the Jendrassik manoeuvre, on muscle spindle sensitivity to passively imposed sinusoidal stretching (1.5 deg, 2 Hz) in relaxed subjects were analysed. The unitary activity of 26 muscle spindle afferents (23 Ia, 3 II) originating from ankle muscles was recorded using the microneurographic method. Particular care was paid to the subjects’ state of physical and mental relaxation. The results showed that the activity of 54 % of the Ia afferents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
93
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(97 citation statements)
references
References 35 publications
3
93
1
Order By: Relevance
“…The decrease of agonist onset latency and antagonist offset latency when WUS indicate a higher performance of the postural control system in this condition. Considering the increase of GM activity (Sousa, et al, 2012) and of postural sway while standing with unstable shoes (Landry, et al, 2010), it can be suggested that the higher performance results from a higher neural drive associated to augmented gamamotoneuron activity that leads to a higher sensitivity of the muscles spindles (Ivanenko et al, 1999;Ribot-Ciscar et al, 2000). Another possibility for the higher postural performance could be an increase of Ia-afferent input onto motoneuron pool of the lower limbs (Loram et al, 2005b) as a result of higher muscle length changes while WUS.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease of agonist onset latency and antagonist offset latency when WUS indicate a higher performance of the postural control system in this condition. Considering the increase of GM activity (Sousa, et al, 2012) and of postural sway while standing with unstable shoes (Landry, et al, 2010), it can be suggested that the higher performance results from a higher neural drive associated to augmented gamamotoneuron activity that leads to a higher sensitivity of the muscles spindles (Ivanenko et al, 1999;Ribot-Ciscar et al, 2000). Another possibility for the higher postural performance could be an increase of Ia-afferent input onto motoneuron pool of the lower limbs (Loram et al, 2005b) as a result of higher muscle length changes while WUS.…”
Section: Discussionmentioning
confidence: 99%
“…TVR derives from the stimulation of Ia-afferents when applying a sinusoidal stimulation directly to a muscle or a tendon (Bongiovanni et al 1990;Fromm 1976;Burke et al 1976). However, TVR seems also to be modulated by alterations in spindle sensitivity through γ control (Matthews 1966;Ribot-Ciscar et al 2000). By applying a vibration directly to the tendon, previous studies have suggested TVR to be composed of motor unit activity synchronized and unsynchronized with the vibration cycle (Hori et al 1989;Romaiguère et al 1991).…”
Section: Introductionmentioning
confidence: 99%
“…We found that target-guided contractions produced more 7-9 Hz coherence among MUs than self-guided contractions, which is consistent with the predicted effects of an increase in the magnitude or gain of afferent feedback. Such a change in afferent feedback and/or fusimotor activity might have stemmed from changes in the cognitive aspects of the task (Hospod et al 2007;Ribot et al 1986;Ribot-Ciscar et al 2000, changes in sympathetic drive (Abila et al 1985), or the change in force dynamics associated with error correction (Marsden et al 1970). Our results suggest that the absence/ presence of a target underlies changes in tremor previously associated with the general absence/presence of visual feedback.…”
Section: Discussionmentioning
confidence: 66%